PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DISERTAI PORTOFOLIOASSESMENT PADA SUB POKOK BAHASAN BANGUN RUANG SISI DATAR UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS VIII-BSMP NEGERI 1 JENGGAWAH - Hanafi, Dwi Sylvia; Suharto, S; Kristiana, Arika Indah (KadikmA, 2014)
Abstract.The purpose of this research are 1) to describe implementation a learning model cooperative NHT with Portofolio Assesment 2) to increase result of mathematic study and studentâs activity to the students of class VIIIB. Cooperative NHT with Portofolio Assesment steps consist of 1) prepared, 2) numbering, 3) Questioning and head together, 4) Answering, 5) Making a conclusion dan 6) give a reward. Type of research is Classroom Action Research (CAR) and the study design used was a model spiral Hopkins, study research design were consists of 4 phases include planning, action, observation and evaluation then reflecting. The object of the research is grade VIIIB students of SMP Negeri 1 Jenggawah and material chosen was Surface Area and volume of Polyhedral. The data collection methods used in this research was observation, test, interview and documentation. From the observation result, in the first class, completeness the student learning outcomes classically is 16,13%. And the second cycle, completeness the student learning outcomes classically is 83,33%. So, from the observation result, teaching and learning process pertained to the active criteria and increased from cycle 1 to cycle 2. Keywords:learning model cooperative NHT with Portofolio Assesment, Lesson plan of NHT, Surface Area and Volume of Polyhedral, Studentâs result study